MALDI-TOF DAN SELDI-TOF MASS SPECTROMETRY DENGAN THROUGHPUT TINGGI UNTUK ANALISIS PROTEOMIK PROFIL PROTEIN DARI PETANDA BIOLOGIS - Trinovia Andayaningsih; Siti Muchayat P. (Indonesian Association of Clinical Pathologist and Medical laboratory, 2016)
In recent years, proteomic approach has been widely used for diagnosing the diseases and matrix assisted laser desorption /ionization- time of the flight (MALDI-TOF) mass spectrometry and its modification, surface enhanced laser desorption /ionization-timeof flight (SELDI-TOF) mass spectrometry have became very promising diagnostic tools. High throughputs and relative simplicity of thesetechnologies attracted the researchers to know the biomarkers of specific diseases by analyzing specimens of serum/plasma and otherbody fluids. Analyzing plasma specimens by MALDI/SELDI TOF mass spectrometry provides new information especially about smallprotein and peptides in high abundance. Protein profilings, resulting by these technologies provide higher sensitivity and specificity valuesthan current biomarkers. Knowing how these principle tools work and its promising application to early detection of specific diseases isthe aim of writing this paper.